Adherence to post-polypectomy surveillance guidelines: a systematic review and meta-analysis - Djinbachian, Roupen; Dubé, Anne-Julie; Durand, Madeleine; Camara, Louopou Rosalie; Panzini, Benoit; Bouchard, Simon; von Renteln, Daniel (Endoscopy, 2019)
Background Colorectal cancer (CRC) is a major worldwide cause of cancer-related mortality. Colonoscopy programs based on guideline-recommended surveillance intervals have been put in place to reduce the morbidity and mortality associated with CRC. We were interested to evaluate clinical practice adherence to guideline-recommended surveillance intervals, the potential extent of early repeat colonoscopies, and causes of nonadherence to guideline recommendations.Methods We performed a literature search for articles reporting on guideline adherence for surveillance colonoscopies. Exclusion criteria included inflammatory bowel disease and hereditary CRC syndrome cohorts. Primary outcome was correct interval assignment in patients undergoing surveillance colonoscopy. Groups were assessed for adherence according to their respective guideline recommendations (North American or European). Results 16 studies were included in the analysis. The mean colonoscopy surveillance interval adherence rate was 48.8 % (95 % confidence interval [CI] 37.3 – 60.4). For North American guidelines, surveillance interval assignments were adherent to guideline recommendations in 44.7 % (95 %CI 24.2 – 66.3) of patients after detection of low risk lesions and in 54.6 % (95 %CI 41.4 – 67.4) after detection of high risk lesions. For European guidelines, surveillance interval assignments were adherent to recommendations in 24.4 % (95 %CI 1.1 – 63.4) of patients after detection of low risk lesions and in 73.6 % (95 %CI 35.5 – 98.8) after detection of high risk lesions. Conclusions The worldwide adherence to surveillance colonoscopy guidelines was low, with more than 50 % of patients undergoing repeat colonoscopies either too early or too late. Early repeat colonoscopies occurred with the highest frequency for patients in whom only hyperplastic polyps or low risk adenomas were found.